Conformational distortion-harnessed singlet fission dynamics in thienoquinoid: rapid generation and subsequent annihilation of multiexciton dark state. Issue 11 (24th February 2022) - Wang, Long; Zhang, Teng-Shuo; Tian, Xiangbin; Guo, Shaoting; Wang, Hua; Cui, Ganglong; Fang, Wei-Hai; Fu, Hongbing; Yao, Jiannian
Abstract : Current work unravels the distinctive conformational distortion-harnessed singlet fission process in thienoquinoid skeleton featuring the rapid generation and subsequent annihilation of intramolecular multiexciton dark state with 2 1 A symmetry. Abstract : Singlet fission (SF) is a multiexciton generation process that could potentially offset thermalization losses and boost the efficiency of photovoltaic devices. However, the scope of SF-active materials still remains rather limited due to the specific energetic requirements and complicated modulation of intermolecular interactions. Therefore, there is a high demand for developing new SF-capable compounds targeted at practical application. In the current work, the SF dynamics of thienoquinoid (TQ), which exhibits high extinction coefficient and excellent stability, were studied systematically based on transient absorption spectroscopy and theoretical calculations. Results present a distinctive conformational distortion-harnessed SF process featuring the rapid generation and subsequent annihilation of intramolecular multiexciton (ME) dark state with 2 1 A symmetry. The increased lifetimes could be achieved via the partially constrained conformational distortion and exciton delocalization in solid or aggregate states, yet these SF-populated ME species cannot undergo effective decoupling and dissociate completely into individual triplet excitons instead, recovering to ground state via the triplet–triplet annihilation channel. These findings present a deeper understanding of SF dynamics in the TQ skeleton, which could be conducive to improving the conversion efficiency of SF-based photovoltaic devices and developing new SF compounds.